Do the Policies and Practices of Teacher Education Serve to Improve Education? A Response Based on the Analysis of the Social Construction of Teaching - Romero Morante, Jesús; Luis Gómez, Alberto (Education Policy Analysis Archives, 2007)
Few people would deny that initial and continuing teacher education are crucial factors in the improvement of education. Nevertheless, one must adopt a certain reservation before offering categorical and knee-jerk responses to the question which heads this article. This is not only a result of the ambiguity of the available evidence, so much the worse if one were to succumb to the temptation of establishing monocausal relationships, but also due to the very complexity of a question whose explicit and implicit terms (?improvement? and its conditions, the ?object? and the ?subject? of the same, the approach to professional preparation, etc.) are all debatable. Moreover, there needs to be some caution in examining the belief that it is feasible to determine empirically the body of knowledge, skills and commitments which would be required by teachers in order to guarantee ?effective? and successful teaching. Given the socio-political nature of institutionalised education, whatever teacher education project must be open to supra-empirical consideration and, for this reason, should be expected to defend itself in accord with general principles. However, these principles or values are proposed; they are not discovered. It follows, therefore, that one inevitably enters into the world of ?discourse?, which tries to persuade by means of arguments and not through the proposal of predictions. On the other hand, in no way does this mean that the problem is reduced to a mere doctrinal choice. The arguments presented neither can nor ought to be divorced from the best knowledge available to us. Precisely for this reason, the authors seek to make a modest contribution to this debate, drawing attention to a body of research which focuses on how professional practice is ?constituted? de facto. It is a body of research too often passed over within this field, despite the fact that it seems fundamental to us in weighing up the possibilities and limitations of teacher education. Its consideration will give us cause to rethink some of the immediate challenges, and to revise (in the light of our findings) the reforms presently being imposed in an effort to redefine professionalism in teaching.